Arabica Coffee Growth Response on Composting Time Treatment and Coffee Skin Biochar Dosage - Yohanes Parlindungan Situmeang; I Gusti Bagus Udayana; I Putu Angga Bismantara (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2022)
This study aims to determine the effect of composting time, biochar dose, and the interaction between composting time and biochar dose on the growth of Arabica coffee seedlings. This research was conducted at UPP Arabica Coffee Plantation. Catur Paramitha in Catur Village, Kintamani District, Bangli Regency, Bali Province. The altitude of the place is between 1,250 meters above sea level. The time of the research was carried out from September to December 2021. This study used a Randomized Block Design (RAK) with 2 factors arranged in a factorial manner. The first factor is the time of composting of wet coffee skin waste material which consists of 2 levels, namely P1 = 2 weeks of composting and P2 = 4 weeks of composting. The second factor is the dose of biochar as raw material for dried coffee cherries, consisting of 4 levels, namely, B0 = control, B1 = 5 tons/ha, B2 = 10 tons/ha and B3 = 15 tons/ha thus obtained 8 repeated combination treatments. 3 times so 24 plants are needed. The variables observed were plant height, number of leaves per plant, stem diameter, plant leaf area, root fresh weight per plant, stem fresh weight per plant, leaf fresh weight per plant, stem, and leaf fresh weight per plant, and total fresh weight per plant. and total oven-dry weight per plant. The treatment with 4 weeks of composting gave the highest total fresh weight per plant, which was 10.43 g, which increased by 11% when compared to the treatment with 2 weeks of composting, which was 9.44 g. The treatment with a dose of 15 tons/ha of biochar gave the highest total fresh weight per plant, which was 10.45 g, which increased by 13% when compared to the treatment without biochar, which was 9.27 g. The interaction of 4 weeks of composting with a dose of 15 tons/ha of biochar (P2B3) gave the highest total fresh weight yield per plant of 11.73 g which increased by 24% when compared to the interaction of 2 weeks of composting without biochar (P1B0) which was 9.4g.